Low-temperature orientational ordering and possible domain structures in C₆₀ - Loktev, V. M.; Khalack, J.N.; Pogorelov, Y.G. (Физика низких температур, 2001)
Based on a simple model for the ordering of hexagons on a square planar lattice, an attempt is made to consider the possible
structure of С₆₀ fullerite in its low-temperature phase. It is shown that hexagons representing fullerenes oriented along the С₃ axes of the sc lattice can be ordered into an ideal structure with four nonequivalent molecules in the unit cell. Then the energy degeneracy for the rotation of each hexagon by π/3 around its С₃ axis leaves the translational and orientational order in this structure but leads to a random distribution of π/3 rotations and hence to an “averaged” unit cell with two molecules. However, the most relevant structural defects are not these intrinsic “misorientations” but some walls between domains with different sequences of the above-mentioned two (nonideal) sublattices. Numerical estimates are made for the anisotropic intermolecular potential, showing that the anisotropy is noticeably smaller for molecules in walls than in domains.